Public universities' guidelines: study on rules and student behavior - Souza Cunha, Victor Henrique [UNESP]; Teixeira, Raphael Nunes [UNESP]; Correa, Janine Coelho [UNESP]; Carrara, Kester [UNESP] (Univ Federal Santa Maria, 2018)
Statutes and regiments are normative texts typically used by public universities to set rules on the functioning of the academic system in various areas. This research intended to identify, describe and analyze rules related to undergraduate teaching in the Statutes and the Regiment of the Sao Paulo State University, aiming to study the effectiveness, descriptive quality and the function of the norms. This analysis is based on the theoretical approach of Behavior analysis, using the Three-Term Contingency as unit of analysis. From the selection of terms (antecedents, responses and consequences) among the norms related to the main subject, 15 contingencies were identified and analyzed, 8 of them incomplete and 7 complete. These were grouped into ceremonial, technological, positive, and negative. We also identified themes to which the contingencies refers to, and the distribution of complete and incomplete contingencies among then: Principles and guidelines; student duties; higher education entry; administrative bodies; curriculum and calendar; collegiate bodies. The results shows how educational (behavioral) rules identified, which composes the educational planning of the studied university, applied to the educational dimension, could be more clear, effective and more democratic in their prescriptions. Results also show that the method used is feasible for describing and analyzing prescriptions, indicating changes that are useful for the designing students' educational processes and the organization of the academic context in several areas.
Keywords: Normative guidelines; Higher education; Behaviorism